The Effect of Job Design on Work Motivation and Employee Behavior - Yuliyansah Putra; Anita Maharani; Mestika Sekarwinahyu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
There are two aims of this research: first, to see the extent to which motivation and work behavior are influenced by job design, and second, to formulate policy proposals related to ideal job design to influence work motivation and behavior. The expected benefits in this research, theoretically, the benefits of this research will contribute to dimensions that are related to work behavior, motivation, and job design. Practically, this research can illustrate case studies that occur in the ward environment and is useful for studying human resource management in local governments. The method of research is through a quantitative approach and apply Partial Least Square as a method to analyze data found by distributing questionnaire through respondents. The respondents involved in this survey were employees from Sumbawa’s apparatus-selected unit. The results did not support all hypotheses. However, this research shows a challenge in exploring factors affecting work motivation and employee behavior.